Population differentiation and epidemic tracking of Bursaphelenchus xylophilus in China based on chromosome‐level assembly and whole‐genome sequencing data. Issue 3 (17th December 2021) - Ding, Xiaolei; Guo, Yunfei; Ye, Jianren; Wu, Xiaoqin; Lin, Sixi; Chen, Fengmao; Zhu, Lihua; Huang, Lin; Song, Xiaofeng; Zhang, Yi; Dai, Ling; Xi, Xiaotong; et al.
Abstract: BACKGROUND: Bursaphelenchus xylophilus, the pinewood nematode, kills millions of pine trees worldwide every year, and causes enormous economic and ecological losses. Despite extensive research on population variation, there is little understanding of the population‐wide variation spectrum in China. RESULTS: We sequenced an inbred B. xylophilus strain using Pacbio+Illumina+Bionano+Hi‐C and generated a chromosome‐level assembly (AH1) with six chromosomes of 77.1 Mb (chromosome N50: 12 Mb). The AH1 assembly shows very high continuity and completeness, and contains novel genes with potentially important functions compared with previous assemblies. Subsequently, we sequenced 181 strains from China and the USA and found ~7.8 million single nucleotide polymorphisms (SNPs). Analysis shows that the B. xylophilus population in China can be divided into geographically bounded subpopulations with severe cross‐infection and potential migrations. In addition, distribution of B. xylophilus is dominated by temperature zones while geographically associated SNPs are mainly located on adaptation related GPCR gene families, suggesting the nematode has been evolving to adapt to different temperatures. A machine‐learning based epidemic tracking method has been established to predict their geographical origins, which can be applied to any other species. CONCLUSION: Our study provides the community with the first high‐quality chromosome‐level assembly which includes a comprehensive catalogue of genetic variations. It provides insights into population structure and effective tracking method for this invasive species, which facilitates future studies to address a variety of applied, genomic and evolutionary questions in B. xylophilus as well as related species. Abstract : Our study provides the community with the first high‐quality long‐read based assembly, a comprehensive catalogue of genetic variations, insights into population structure and effective tracking method for Bursaphelenchus xylophilus . © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.